High-Voltage Flexible Aqueous Zn-Ion Battery with Extremely Low Dropout Voltage and Super-Flat Platform - Chen, Zhe; Wang, Panpan; Ji, Zhenyuan; Wang, Hua; Liu, Jie; Wang, Jiaqi; Hu, Mengmeng; Huang, Yan (Nano-Micro Letters, 2020)
Flexible rechargeable aqueous zinc-ion batteries (ZIBs) have attracted extensive attentions in the energy storage field due to their high safety, environmental friendliness, and outstanding electrochemical performance while the exploration of high-voltage aqueous ZIBs with excellent rate capability is still a great challenge for the further application them in flexible and wearable electronics. Herein, we fabricated a 2.4 V high-voltage flexible aqueous ZIB, being among the highest voltage reported in aqueous ZIBs. Moreover, it exhibits extremely flat charging/discharging voltage platforms and the dropout voltage is only 0.1 V, which is the smallest gap in all aqueous batteries to our best knowledge. Furthermore, the prepared ZIB performs high rate capability of 25 C and energy density of 120 Wh kg−1 and exhibits excellent safety under various destructive conditions including hammering, sewing, punching, and soaking. These extraordinary results indicate the great application potential of our high-voltage flexible aqueous ZIB in wearable electronics. Highlights: 1 A 2.4 V high-voltage flexible aqueous ZIB was fabricated, and superiors performances were achieved: extremely flat charging/discharging voltage plateaus (1.9/1.8 V), the smallest plateau voltage gap of 0.1 V, high energy density of 120 Wh kg−1, high power density of 3700 W kg−1, and excellent rate capability of 25 C. 2 The battery posed application potential in wearable electronics with extreme safety against tough destructions including hammering, sewing, punching, and soaking.